Isolation and identification of dye degrading bacteria from the Textile Sludge (Soil) sample - Pramanik, Chinmay (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2014.